2020
DOI: 10.1007/s13770-020-00294-0
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Physiological Studies of the Effect of Bone Marrow-Derived Mesenchymal Stem Cells on Bleomycin Induced Lung Fibrosis in Adult Albino Rats

Abstract: Background: Lung fibrosis is considered as an end stage for many lung diseases including lung inflammatory disease, autoimmune diseases and malignancy. There are limited therapeutic options with bad prognostic outcome. The aim of this study was to explore the effect of mesenchymal stem cells (MSCs) derived from bone marrow on Bleomycin (BLM) induced lung fibrosis in albino rats. Methods: 30 adult female albino rats were distributed randomly into 4 groups; negative contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
(63 reference statements)
3
16
0
Order By: Relevance
“…Morphometric measurement after 7 days, the mean thickness of the interalveolar septa in (µm) and the mean alveolar space surface area (µm 2) after 7 days As the same mentioned in morphometric analysis (Zakaria et al, 2021). Blind histological analysis was performed on the lung paraffin sections from mice after 7 days for estimation of parenchymal distortion and airway (peribronchial) inflammation using specific semi-quantitative scores: Analysis of Lung parenchymal distortion: It was assessed by analysis of ten sequential non-overlapping tissue fields using x200 magnification.…”
Section: Immuno-histochemical Analysis For Bcl-2 At Day 7 and At Day 28 Post-treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Morphometric measurement after 7 days, the mean thickness of the interalveolar septa in (µm) and the mean alveolar space surface area (µm 2) after 7 days As the same mentioned in morphometric analysis (Zakaria et al, 2021). Blind histological analysis was performed on the lung paraffin sections from mice after 7 days for estimation of parenchymal distortion and airway (peribronchial) inflammation using specific semi-quantitative scores: Analysis of Lung parenchymal distortion: It was assessed by analysis of ten sequential non-overlapping tissue fields using x200 magnification.…”
Section: Immuno-histochemical Analysis For Bcl-2 At Day 7 and At Day 28 Post-treatmentmentioning
confidence: 94%
“…Morphometric analysis after 28 days: measurement of the area percent of collagen fibers in Masson trichrome stain as same mentioned (Zakaria et al, 2021).They were measured by using the NIH Image J (v1.50) program and measurement of subepithelial connective tissue volume density (VVsub) in Masson trichrome stain after 28 days. Airway wall remodeling was evaluated by measurement of VV sub as the difference in the area, delimited by the basement membrane and the outer edge of the airway adventitia, divided by the length of subepithelial basement membrane (Polosukhin et al, 2012).…”
Section: Immuno-histochemical Analysis For Bcl-2 At Day 7 and At Day 28 Post-treatmentmentioning
confidence: 99%
“…Morphometric measurement after 7 days, the mean thickness of the interalveolar septa in (µm) and the mean alveolar space surface area (µm 2) after 7 days As the same mentioned in morphometric analysis (Zakaria et al, 2021). Blind histological analysis was performed on the lung para n sections from mice after 7 days for estimation of parenchymal distortion and airway (peribronchial) in ammation using speci c semi-quantitative scores: Analysis of Lung parenchymal distortion: It was assessed by analysis of ten sequential non-overlapping tissue elds using x200 magni cation.…”
Section: Tissue Homogenatementioning
confidence: 94%
“…More recently, it was demonstrated that chronic Wnt/β-catenin activity in the IPF lung increased AECII senescence, leading to further progenitor cells dysfunction and impaired lung repair (Lehmann et al, 2020). In contrast, previous studies have shown that a particular lineage of Wnt responsive alveolar epithelial progenitor cells within the AECII population acted as a central player in lung regeneration after acute injury, being able to self-renew (Zacharias et al, 2018). Bolanos et al (2012) found that Shh pathway is activated in IPF lungs and might contribute to IPF pathogenesis by increasing fibroblast proliferation, migration and ECM production.…”
Section: Tgfβ Signaling and Cross-talk With Wnt And Sonic Hedgehog Pathways Activated In Epithelial Cells Of Idiopathic Pulmonary Fibrosimentioning
confidence: 99%
“…As IPF is usually diagnosed only after extensive fibrotic changes are present, this raises questions as to whether MSCs administration will be beneficial in IPF. However, in a recent study from Zakaria et al in albino rats BM-MSCs systemically administered 28 days after bleomycin-induction of lung damage; resulted in reversion of established fibrosis, restored lung architecture, and improved lung functions ( Zakaria et al, 2021 ). The mechanisms by which these effects occurred need further study and may open up better understanding that will support use of systemically administered MSCs in IPF.…”
Section: The Role Of Exogenously Administered Mesenchymal Stromal/stem Cells In Lung Repair After Injurymentioning
confidence: 99%